CARD READER - RISTYAWATI RISTYAWATI RISTYAWATI (Majalah SIKOMTEK, 2005)
The rapid development of electronic world-sized chips are currently produced many havebeen implemented in a card-card technology that will replace the previously used magneticdata. With the addition of the processor chip in a data card allows card data to further processthe data contained in it so many additional features such as additional data security featuresand other applications become increasingly easy to do.Card Reader Technology has entered a new phase, with a starting number of applications thatare built based card reader resulted in a lot of hardware manufacturers to produce devicescard reader, but to get the card reader is still to be imported. Also generally Card Reader onthe market still need a computer card reader because it was designed for a variety ofapplications that need to be flexible with the application to be built by the consumer.